Proposed new interior design of An Nur Syada salon at No. 9A -11A,Jalan Plumbum P7/P, 40000 Shah Alam, Selangor Darul Ehsan for An Nur Syada Enterprise / Nurfarah Ezzah Mohd Atan - Mohd Atan, Nurfarah Ezzah (Faculty of Architecture, Planning and Surveying, 2012)
The final project for the final year students of Interior Architecture is based on the knowledge gained from the past five semesters. Those lessons that have been learnt are compiled together to be put to the test by self by proposing a final project based on the real life. The chosen project then will go through the process of analysing and designing before it completely go throught the final process which is to confirm the final design. Besides that, the chosen project must have general and design issues as the project reinforcement. The articles from the newspapers, magazine, internet and also through the interview session are compiled together to make them as an evidence that supports the project. Other than that, the problems that have been identified from the observation that student has go through at the existing site must be resolved and must be proved at the final. So that, the process of planning and more research are needed to ensure that the problems will be solved. Therefore, planning and research are required to ensure that the project run smoothly and students couId have a greater understanding about the project they proposed.